Evaluation of objective response, disease control and progression-free survival as surrogate end-points for overall survival in anti–programmed death-1 and anti–programmed death ligand 1 trials. (January 2019) - Nie, Run-Cong; Chen, Fo-Ping; Yuan, Shu-Qiang; Luo, Ying-Shan; Chen, Shi; Chen, Yong-Ming; Chen, Xiao-Jiang; Chen, Ying-Bo; Li, Yuan-Fang; Zhou, Zhi-Wei
Abstract: Background: We aimed to assess whether the Response Evaluation Criteria in Solid Tumors (RECIST) criteria–based objective response rate (ORR), disease control rate (DCR) and progression-free survival (PFS) could be valid surrogate end-points for overall survival (OS) in anti–programmed death-1 (PD-1)/programmed death ligand 1 (PD-L1) trials. Methods: We systematically reviewed phase 2 and phase 3 trials of anti–PD-1/PD-L1 drug trials of advanced or recurrent solid tumours that reported OS and at least one of the RECIST criteria–based end-points. We used Spearman rank correlation to evaluate the strength of the association between these end-points and OS and a linear regression model, weighted by the sample size, to assess the association between the treatment effect on these end-points and OS. We also performed sensitivity analyses and a leave-one-out cross-validation approach to evaluate the robustness of our findings. Results: Forty-three qualifying trails comprising 15, 088 patients were eligible. PFS showed good correlation with OS (squared Spearman rank correlation coefficient [ r s 2 ] = 0.54; P < 0.001), while ORR and DCR illustrated moderate association with OS ( r s 2 = 0.29 and 0.28, respectively; both P < 0.001). The correlation was moderate between the treatment effects on PFS and OS (coefficient of determination [ R 2 ] = 0.37, P < 0.001) and poor among ORR, DCR and OS ( R 2 = 0.10 and 0.08, respectively); these were confirmed by sensitivity analyses (all R 2 < 0.75) and the leave-one-out cross-validation approach. Conclusions: No RECIST criteria–based end-points could be a valid surrogate for OS. At present, we proposed to set OS as the primary end-point in anti–PD-1/PD-L1 drug trials of advanced or recurrent solid tumours. Highlights: None of the Response Evaluation Criteria in Solid Tumors (RECIST) criteria–based end-points could be a valid surrogate for overall survival (OS). Optimisation of the RECIST criteria in immunotherapy trials is still urgently needed. OS should still be set as the primary end-point in anti–programmed death-1/programmed death ligand 1 drug trials.